The Conditions of Pedagogical Tolerance Development in Modern School - Ohorodniichuk, Iryna (Pedagogical Discourse, 2016)
The article reveals the foundations of theoretical-methodological concepts of teaching tolerance in schools and justify the conditions for its development. The theoretical basis of this study are the provisions in existential-humanistinen M approach. M. Bakhtin, H. A. Berdyaev, N. Heidegger, K. Rogers, A. Maslow; pedagogical anthropology, B. G. Ananiev, L. M. Tolstoy, J. A. Komensky, K. D. Ushinsky, E. Fromm; psychology of tolerance of A. G. Asmolov, C. JI. Bratchenko; educational psychology M. D. Levitov, E. I. Kirshbaum, L. M. Mitina; pedagogy of tolerance. G. Gurov, E. Y. Kleptsov; theory of pedagogic communication N. Bakhtin, A. A. Leontiev etc. In modern science, there are developments that point to the specificity of the phenomenon of tolerance, reveal the components of its formation (target, motivational, informative, technological, monitoring, regulating) and justify pedagogical principles of tolerance (G. Burns, S. Bamer, A. Dubbink, V. Ishchenko, V. Lecturing, etc.). In the context of the pedagogy of tolerance is interpreted as a willingness to accept others for who they are, and interact with them on the basis of agreement and Concord (A. Beznosyuk, S. Boldyrev, S. Burdin, V. Kaloshin). Tolerance within the proposed discourse should be understood as a professionally important quality of a teacher which is characterized by the ability to perceive without aggression other thoughts, a different way of life, behavior, appearance and other features of educational, social and cultural space by establishing with them relations of trust, cooperation, compromise, joy, empathy and psychological comfort. Measured and analyzed parameters of tolerant interaction between student and teacher: dialogue, cooperation, care and forgiveness. It is argued that the criteria of formation of tolerance of future teachers as professionally important qualities of their personality are facilitative position: focus on personal interaction model, the congruence and the absence of any forms of aggression in educational process. Identified psychological and pedagogical conditions of forming tolerance in the interpersonal relationships of the future teachers. Stages of formation of tolerance among future teachers: motivational, substantive and procedural. The analysis of the models achieve a three-level teacher of intercultural competence. Key words: tolerance, education, modern school teacher.